Perancangan Interior Cokro Cooking Studio Di Jakarta - Tiara Putri Fadhilah; Irma Damayantie (Journal of Innovative and Creativity, 2025)
At this time the culinary is in great demand by the wider community. Many people are interested in exploring their cooking skills by learning form recipes on the internet or by gathering with cooking experts who share the same hobbies. Interest in the world of cooking is also not limited to adults, not a few children are interested in cooking activities. The method used in the design of Cokro Cooking Studio uses a qualitative research method with a case study approach that prioritizes observation and research on objects that will become research material in accordance with field facts. This is proven by the existence of television show program Masterchef a cooking competition which has been aired in 2011 until now and even for junior participants who have a hobby of cooking which has aired in 2014. However, there are still few facilities available to support interest in cooking. Cooking studio is a place used for cooking courses. Not infrequently the cooking studio also provides a café or bar that can be enjoyed by the public. Interest in cooking is not only directed at adults, but many children are also starting to be interested in this cooking activity. With the existence of a cooking studio, it can facilitate and realize people's interest in cooking.